The health impact of identifying a person with tuberculosis through systematic screening - Kendall, Emily A; Dowdy, David W (The Lancet infectious diseases, 2025)
Screening populations at high risk for tuberculosis might improve clinical outcomes and reduce transmission, but the value and cost-effectiveness of population-based screening depend on the uncertain health impact of early tuberculosis detection. In this Personal View, we propose a framework for estimating the incremental health impact of systematic screening, including effects on tuberculosis morbidity, mortality, sequelae, and transmission. Our framework accounts for the timing of screening, relative to when routine diagnosis might occur and when health effects become inevitable. We also account for the heterogeneous duration of tuberculosis, as people with longer disease courses (associated with lower mortality but more transmission) are more likely to be detected by screening. Finally, we use this framework to estimate that population-based chest x-ray screening interventions might avert 2·4 disability-adjusted life-years per person (95% uncertainty interval 0·8-7·4) found to have tuberculosis through screening-well within the cost-effectiveness thresholds for many programmes with published costs.